Efektivitas Beberapa Obat Antimalaria Terhadap Plasmodium Falciparum di Donggala, Sulawesi Tengah=Effectiveness of Antimalaria Drugs Due to Plasmodiutn Falciparum in Donggala, Central Sulawesi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Malaria still occurs as one of the health problems in the world. Central Sulawesi province occupied as the worst sixth out of 27 provinces in Indonesia. Donggala regency included as malaria endemic area and considered had the greatest number of ambulatory care in Puskesmas. In Donggala regency sensitivity of P. falciparum toward chloroquine was about 86% and toward sulfadoxine+pyrimethamine was 50%. Based on this fact, this study was aimed to investigate the effectiveness of some anti-malaria drugs. This study was implemented in five Puskesmas. The population of this study was chosen from Puskesmas visitors who had malaria clinic syndrome. Furthermore, subjects of this study were parasitemia sufferers with asexual stadium. Exclusion criteria consists of